2013
DOI: 10.1007/s10439-013-0860-0
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Function and Adhesion Mechanisms of Human Bone Marrow Mesenchymal Stem Cells on Multi-walled Carbon Nanotubes

Abstract: Multiwalled carbon nanotubes (MWCNTs) are considered to be excellent reinforcements for biorelated applications, but, before being incorporated into biomedical devices, their biocompatibility need to be investigated thoroughly. We investigated the ability of films of pristine MWCNTs to influence human mesenchymal stem cells' proliferation, morphology, and differentiation into osteoblasts. Moreover, the selective integrin subunit expression and the adhesion mechanism to the substrate were evaluated on the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…Our results 12 showed that MWCNTs substrates decreased cell numbers but displayed an accelerated progression of osteoblast phenotype development, indicated by early and enhanced expression of alkaline phosphatase activity (ALP) and osteocalcin (OC) and osteopontin (OP) levels. In the absence of additional biochemical inducing agents, ALP on MWCNTs increased about fold4-as that on the control.…”
Section: Mwcnts Delay the Proliferation Of Hbmsc Cells But Increase Tmentioning
confidence: 84%
See 2 more Smart Citations
“…Our results 12 showed that MWCNTs substrates decreased cell numbers but displayed an accelerated progression of osteoblast phenotype development, indicated by early and enhanced expression of alkaline phosphatase activity (ALP) and osteocalcin (OC) and osteopontin (OP) levels. In the absence of additional biochemical inducing agents, ALP on MWCNTs increased about fold4-as that on the control.…”
Section: Mwcnts Delay the Proliferation Of Hbmsc Cells But Increase Tmentioning
confidence: 84%
“…1 shows cell spreading on MWCNTs and TCP by fluorescent staining of the cytoskeleton f-actin (green) and DNA (blue). From data presented in Kroustalli et al, 12 areas of lower cell density were selected to facilitate observation of individual cell shapes. The images of the cells shown in the selected micrographs are typical of cells throughout the culture.…”
Section: Mwcnts Delay the Proliferation Of Hbmsc Cells But Increase Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, CNTs have already been used as scaffolds for cellular or tissue growth. 2,[5][6][7] However, the essential impediments to their use in medicine continue to be uncertain about their biological safety and their influence on the human health. Although its cytotoxicity has been extensively studied, both in vivo and in vitro, as reviewed by Kayat et al,8 there are some contradictory results that can be attributed to the use of materials with different degrees of purity and structural features, 9 as well as to the conditions adopted for the in vitro studies 10 and the types of cells tested in the assays.…”
Section: Introductionmentioning
confidence: 99%
“…A focus is to use nanotubes, which reproduce the structure and length scale of bone native topography and may act as an exceptional substrate for cell growth and differentiation. 5,6 The research advances in the use of nanotubes as reinforcing agents in developing nanocomposites with synthetic and natural biodegradable polymers are reviewed. The extent of mechanical reinforcement of the polymers and the corresponding biological response of the nanocomposites are presented.…”
Section: Introductionmentioning
confidence: 99%